Bridging the gap: A new species of arboreal Abronia (Squamata: Anguidae) from the Northern Highlands of Chiapas, Mexico. - Adam G Clause; Roberto Luna-Reyes; Oscar M Mendoza-Velázquez; Adrián Nieto-Montes de Oca; Israel Solano-Zavaleta (PLoS ONE, 2024)
The mountain forests of Middle America are renowned for their endemic biodiversity, and arboreal alligator lizards (genus Abronia) are high-profile vertebrates endemic to this region. In this work, we describe a new species of arboreal Abronia that is known only from the type locality in the Northern Highlands of Chiapas, Mexico. The new species is diagnosed from all other members of the genus Abronia by the following combination of characters: lack of protuberant or spine-like supra-auricular scales, lack of protuberant or casque-like posterolateral head scales, dorsum of head pale yellow with distinct dark markings, 35-39 transverse dorsal scale rows, lateralmost row of ventral scales enlarged relative to adjacent medial row, and dorsum brown with darker crossbands that are sometimes reduced to rows of spots. We provisionally include the new species in the subgenus Lissabronia based on genomic and morphological evidence, but our results also suggest a close relationship to the subgenus Abaculabronia. The new species is geographically separated from the nearest Lissabronia and Abaculabronia species by the lowland Central Depression of Chiapas. Ongoing habitat loss and other factors imperil the new species, leading us to propose its listing under multiple threatened species frameworks. Because the Northern Highlands have poor coverage of protected areas, we briefly comment on the potential of this new species for stimulating conservation in the region.